Les cinéphonies, des « chefs-d’œuvre expliqués par l’image » ? - Inès Taillandier-Guittard (Itinéraires)
In the mid-1930s, Émile Vuillermoz supervised the production of a series of seven short films produced by the Compagnie des Grands Artistes Internationaux (CGAI). These so called cinéphonies are considered in existing literature to be the ancestors of videoclips. This term refers to an audiovisual object whose aim is twofold. On the one hand, the performers are filmed (the “technical film”), and on the other hand the performed work is transposed cinematographically (the cinéphonie itself). This article examines the status of these short films, which serve both didactic and promotional aims. It also attempts to consider the visual medium not as a pure mirror of sound (however complex this specular relationship may be), but as the fruit of successive metamorphoses that generate their own logic, within and between shots. Three cinéphonies will be analyzed in detail: La Fontaine d'Aréthuse and Jeune fille au jardin by Dimitri Kirsanoff, and La Valse Brillante de Chopin by Max Ophuls